2012
DOI: 10.1111/j.1365-3156.2012.02989.x
|View full text |Cite
|
Sign up to set email alerts
|

Unvaccinated children in years of increasing coverage: how many and who are they? Evidence from 96 low‐ and middle‐income countries

Abstract: Abstractobjective While childhood immunisation coverage levels have increased since the 70s, inequities in coverage between and within countries have been widely reported. Unvaccinated children remain undetected by routine monitoring systems and strikingly unreported. The objective of this study was to provide evidence on the magnitude of the problem and to describe predictors associated with nonvaccination.methods Two hundred and forty-one nationally representative household surveys in 96 countries were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
73
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 10 publications
10
73
0
1
Order By: Relevance
“…Others have found poor socioeconomic development, a weak health care system and high socio-cultural barriers to care utilization as associated risk factors for the high rate of maternal and child mortality in Nigeria (Ogunjimi et al, 2012); people's beliefs, attitudes and behavioural practices (Ogunjuyigbe, 2004) add to the burden. Bosch-Capblanch et al (2012) found caregiver's and partner's education, and caregiver's tetanus toxoid status to be strongly associated with being unvaccinated. Also, Kayode et al (2012) reported that the mother's age at first marriage plays an important role in reducing underfive mortality in Nigeria; other favourable practices include health-seeking behaviour, breast-feeding children for more than 18 months, use of contraception, small family size, having one wife, low birth order, normal birth weight, child spacing, living in urban areas and good sanitation.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Others have found poor socioeconomic development, a weak health care system and high socio-cultural barriers to care utilization as associated risk factors for the high rate of maternal and child mortality in Nigeria (Ogunjimi et al, 2012); people's beliefs, attitudes and behavioural practices (Ogunjuyigbe, 2004) add to the burden. Bosch-Capblanch et al (2012) found caregiver's and partner's education, and caregiver's tetanus toxoid status to be strongly associated with being unvaccinated. Also, Kayode et al (2012) reported that the mother's age at first marriage plays an important role in reducing underfive mortality in Nigeria; other favourable practices include health-seeking behaviour, breast-feeding children for more than 18 months, use of contraception, small family size, having one wife, low birth order, normal birth weight, child spacing, living in urban areas and good sanitation.…”
Section: Introductionmentioning
confidence: 85%
“…In his study, Antai (2009) employed the use of a three-level multi-level logistic regression model to assess the risk factors for childhood immunization in Nigeria in 2003 using DHS data at the child level nested within mothers who were in turn nested within com-munities. Bosch-Capblanch et al (2012) carried out a logistic regression analysis on data from 241 nationally representative household surveys in 96 countries using the unique or most recent survey for each country. They dichotomized the vaccination status as children having not received any vaccination ('unvaccinated') vs children who had received at least one dose (partially vaccinated) of any vaccine and fully vaccinated children.…”
mentioning
confidence: 99%
“…The quality of studies was assessed using criteria adapted from several quality assessment tools for qualitative (Bedford et al 2013;Critical Appraisal Skills Programme (CASP) 2014) and quantitative studies (Effective Public Health Practice Project 2010; Jackson et al 2005).…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Accomplishing these goals requires efforts at community level and in each tier of health systems and globally. Under-and no-vaccination remains a problem in many countries (Bosch-Capblanch et al 2012), a challenge not only for health systems, but also for communities and families. Vaccination coverage has been increasing in the last decades worldwide; however, Sub-Saharan Africa coverage rates remain constantly below other regions, and countries within it show large disparities in coverage (WHO 2014d).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of 126 documents from the global grey literature cited many barriers of incomplete child vaccinations, including poor access to services, unsupportive health staff attitudes, parents' poor practical knowledge of vaccination, and fear of side effects [23]. On the other hand, antenatal care follow-up, being born in a health facility and wealth index, have been associated with vaccination status [24,25]. The many socio-demographic factors associated with immunisation coverage in recent research include ethnicity and religion [26], caregiver's education [27], household economic status [28,29], maternal health literacy [29], maternal decision latitude [30], use of maternal and child health facilities [27], participation in vaccination campaigns [31] and urban versus rural living [32].…”
Section: Introductionmentioning
confidence: 99%